Strategic International Management Text and Cases - Morschett, Dirk.; Schramm-Klein, Hanna; Zentes, Joachim; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
(3z(BStrategic International Management(3y (Btakes a global perspective and covers the major aspects of international business strategies. It introduces the complexity of international business based on the perspective of Multinational Corporations as inter-organisational and intra-organisational networks. The authors highlight the role of the external environment, discuss the major coordination mechanisms and organisational structures and examine various foreign operation modes. The book describes the particularities of international value chain activities and management functions and offers a thorough understanding of how Production & Sourcing, Research & Development, Marketing, Human Resource Management and Controlling have to be designed in an international company and what models are available to understand those activities in an international context. In 20 lessons, a comprehensive overview of all key issues is given. Each lesson is accompanied by a case study from an international company to facilitate the understanding of all important factors involved in strategic international management. In this second edition, all chapters have been updated, all case studies revised and recent data were integrated. The concept, though, remained unchanged. Contents Introduction to Strategic International Management The External Environment International Coordination Foreign Operation Modes Selected Value Chain Activities Selected International Business Functions Target Groups Advanced undergraduate students and graduate students majoring in international management or general management Practitioners who wish to obtain compact and practice-oriented information on current concepts About the Authors Dirk Morschett is Professor of International Management at the University of Fribourg, Switzerland. Hanna Schramm-Klein is Professor of Marketing at the University of Siegen, Germany. Joachim Zentes is Professor of Management and Marketing at the Saarland Univs
& Basic Definitions -- & Basic Definitions -- to Strategic International Management -- Multinational Corporations as Networks -- The Integration/Responsiveness-Framework -- Role Typologies for Foreign Subsidiaries -- Motives for Intelnationalisation -- The External Environment -- Market Barriers, Global and Regional Integration -- Competitive Advantage of Nations and Regional Clusters -- The Role of Country Culture for International Management -- International Coordination -- Formal and Informal Coordination Mechanisms -- International Organisational Structures as Coordination Mechanism -- Corporate Culture as Coordination Mechanism -- Corporate Social Responsibility of MNCs -- Foreign Operation Modes -- Basic Types and Theoretical Explanations of Foreign Operation Modes -- Buying, Outsourcing and Offshoring -- International Alliances -- Wholly-owned Subsidiaries, Greenfield Investments, Mergers & Acquisitions -- Selected Value Chain Activities -- International Production & Sourcing -- International Research & Development -- International Marketing -- Selected International Business Functions -- International Human Resource Management -- International Control.
Keywords: Economics; Industrial management; Marketing; Economics/Management Science; Management/Business for Professionals; Management/Business for Professionals; Marketing